There are many options, but substitution is the one we will go through for this example first. Lets say you have 3x+4y = 10 and x+2y = 6In this case substitution would be easiest because you have a singular 'x' in one of the equations. Make x the subject of the second equations so that x = 6 - 2y, and then *substitute *this into the first equation 3(6 - 2y) + 4y = 10 to give you 18 - 2y = 10. From here simplify to find y: 8 = 2y therefore y = 4. then find x; x = 6 - 2y. x = 6 - 8 therefore x = -2.